ANALISIS KEBERHASILAN KERJA ULANG PINDAH LAPISAN PADA SUMUR SKW-33 LAPANGAN SUKOWATI - Desyana Nindya Prastiwi; Abror, Hadziqul; Hafwandi, Babas samudera (Petroleum Engineering, Faculty of Engineering, University of Jember, 2024)
This study explores the effectiveness of re-perforation operations at Well SKW-33 in the Sukowati Field to enhance oil production. The background highlights the decline in production rates despite the well's initial success with natural flow since June 2015. The primary objective is to evaluate the impact of re-perforation on oil production and water cut. The research employs methods such as squeeze cementing, Cement Bond Log (CBL) analysis, well logging and subsequent re-perforation. The results demonstrate a significant increase in oil production from 100-150 barrels per day (bopd) to a peak of 305 bopd post-re-perforation. Additionally, the water cut reduced from 95-96% to 80%, indicating a successful reduction in water production. The conclusion asserts that re-perforation significantly boosts short-term oil production and reduces water production, though ongoing management is essential for maintaining long-term efficiency.